Kebijakan Energi untuk Rakyat: Subsidi LPG 3 Kg dan Tantangannya di Jawa Barat - Riki Satia Muharam; Budiman Rusli; Nina Karlina; Candradewini Candradewini (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the implementation of the 3-kg LPG subsidy policy in West Java Province and to identify the challenges faced in its distribution and monitoring. Using a descriptive qualitative approach, data were collected through in-depth interviews with key informants and documentation studies. The findings show that the 3-kg LPG subsidy policy has had a positive impact in reducing household energy expenses for low-income families, improving quality of life, and expanding access to clean energy. However, several serious challenges still hinder the effectiveness of the policy, including inaccuracies in targeting subsidy recipients, uneven distribution, weak distribution infrastructure, poor local monitoring, and the emergence of speculative practices and gas mafia activities. The role of local governments in updating data, conducting socialization, and enforcing regulations needs to be strengthened to ensure the subsidy reaches its intended targets. Policy recommendations include the adoption of digital technologies for distribution monitoring, regular updating of recipient data, strengthening of supervision, community empowerment in distribution monitoring, enhancing transparency, and fostering collaboration among government, private sector, and society. With improvements in these areas, the distribution of the 3-kg LPG subsidy is expected to become more equitable, effective, and supportive of Indonesia’s sustainable energy transition agenda.